Sermons, Controversy, and Community Resilience in Surakarta Mosques - Annur, Muhammad Syihabuddin (Jurnal Sosiologi Agama, 2024)
This reasearch aims to explore the forms of controversial religious narratives in the Sagara and Jagananta Mosques in Surakarta, as well as the congregation’s responses to these narratives. The research location is significant because both mosques have been involved in the emergence of an Islamic purist group associated with intolerance and radicalization. The study uses a qualitative method with an ethnographic approach and content analysis, through observations and interviews with eleven mosque members representing the surrounding community. The findings indicate that the controversial narratives emerging in Friday sermons and religious lectures include one-sided condemnations of government policies, political views of other groups, and the demonization of certain communities. In general, the congregations in both mosques demonstrate resilience by questioning and rejecting these narratives, relating them to more official and legitimate sources of information. They respond realistically, rejecting calls such as the condemnation of anti-terrorism laws and the belief that online games are a Jewish attack. Conversely, some more vulnerable members of the congregation affirm these narratives, influenced by feelings of victimization and shared political views. These findings suggest a contestation of religious orientations, which has implications for social transformation within the community.